Determination of exports of the floriculture sector of the municipality of Rionegro, Antioquia - Duque - Castaño, Yeny Paola (Universidad Francisco de Paula Santander, 2021)
Flower exports represented for Colombia during 2020, total sales of 1,393 million, evidencing the importance of the sector for the national economy, which generates more than 120,000 direct jobs, mainly linking mothers who are heads of household and rural female population. Cundinamarca is consolidated as the first flower production center, followed by Antioquia, where most of the crops are located in the Oriente Antioqueño subregion. Being this one of the nine subregions that make up the department, it enjoys varied climates that allow it to have a strong agricultural vocation for having crops of fruits, vegetables and flowers. Likewise, it has 23 municipalities which are divided by zones, such as paramos, reservoir, forests and Valle de San Nicolás; the latter, with 9 municipalities, including Rionegro, which stands out for its economic development and business settlement, where a large part of the flower export crops is also housed. According to the commercial registry of the Oriente Antioqueño Chamber of Commerce, for the year 2019, 43 companies were authorized as flower exporters, which were analyzed to determine the target market, the exported FOB value, products and shipping areas of the merchandise.